Microbially mediated nutrient cycles in marine sponges. Issue 11 (7th October 2019) - Zhang, Fan; Jonas, Lauren; Lin, Hanzhi; Hill, Russell T
ABSTRACT: Efficient nutrient cycles mediated by symbiotic microorganisms with their hosts are vital to support the high productivity of coral reef ecosystems. In these ecosystems, marine sponges are important habitat-forming organisms in the benthic community and harbor abundant microbial symbionts. However, few studies have reviewed the critical microbially mediated nutrient cycling processes in marine sponges. To bridge this gap, in this review article, we summarize existing knowledge and recent advances in understanding microbially mediated carbon (C), nitrogen (N), phosphorus (P) and sulfur (S) cycles in sponges, propose a conceptual model that describes potential interactions and constraints in the major nutrient cycles, and suggest that shifting redox state induced by animal behavior like sponge pumping can exert great influence on the activities of symbiotic microbial communities. Constraints include the lack of knowledge on spatial and temporal variations and host behavior; more studies are needed in these areas. Sponge microbiomes may have a significant impact on the nutrient cycles in the world's coral reef ecosystems. Abstract : Microbial symbionts associated with marine sponges are important mediators of nutrient cycles in benthic coral reef ecosystems.